Integrating social customer relationship management into customer relationship management processes in academic library - Alilou, Farima (2014)
Social Customer Relationship Management (SCRM) is a novel concept that unites social media technology with customer relationship management. It is essential that libraries in academic environments and their members require some specific means to strengthen the related communications between instructors, students, and librarians of the academic environments. This study aims to integrate SCRM characteristics into CRM processes in the library context. A case study was conducted at UTM library (PSZ). The characteristics of social CRM and CRM processes are explored from several case studies in literature review. The characteristics of SCRM are applied to CRM processes in an initial Library Social Customer Relationship Management (LSCRM) framework. In order to refine and verify the framework, interviews with expert librarians and customers of PSZ library were conducted. Qualitative data analysis was done to finalize the framework. The proposed LSCRM framework mapped SCRM characteristics into CRM processes with some social network tools which are appropriate for PSZ library. This study also made recommendations for improving the existing Customer Relationship Management by applying SCRM concept for PSZ library. The outcomes of this study may pave the way to socializing processes in academic libraries for better connection and relationship with customers.